GENEOLOGI DAN ETNOGRAFI MASYARAKAT ADAT DI INDONESIA: STUDI KASUS SUKU TOGUTIL, BADUY DAN SAKAI - Munandar Munandar; Kiki Mikail (Program Studi Sejarah Peradaban Islam UIN Raden Fatah Palembang, 1970)
This research is qualitative research that seeks and expolore how indigenous peoples particularly in Indonesia such as Togutil, Baduy and Sakai tribes identify themselves as a small group that occupies a certain area. The Togutil tribe, who hails from north Halmahera, tries to explore nature by utilizing various types of wood, bark, roots, rigging, and leaves to mix medicins. Many Indonesian people are also interested in doing healing therapy with traditional medicines In addition, the Baduy tribe practice living with the pikukuh karuhun pattern (traditional), for example they are only allowed to wear clothes with two colors black and white. The village of the inner Baduy is considered a prototype of the ancient Sundanese village, which extends on both sides of a field and then at both ends there are two main buildings facing each other, one is the bale (receive guests) and other is the pu’un (leader) building. Baduy community). The Sakai tribe in their life recognizes three important stages in the life process. The first is the period of pregnancy and childbirth, then the second is the period of marriage and the last is the period of death. Each stage will be carried out a ceremony that is run by the family